2004
DOI: 10.1007/s10350-004-0711-z
|View full text |Cite
|
Sign up to set email alerts
|

Robotic and Laparoscopic Surgery for Treatment of Colorectal Diseases

Abstract: Robot-assisted surgery proved to be as safe and effective as laparoscopic techniques in the treatment of colorectal diseases. Because of its dexterity and three-dimensional view, the da Vinci system was particularly useful in specific stages of the procedure, e.g., takedown of the splenic flexure, dissection of a narrow pelvis, identification of nervous plexus, and handsewn anastomosis. The cost-effectiveness of the procedure still needs to be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
248
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(274 citation statements)
references
References 15 publications
16
248
0
8
Order By: Relevance
“…Robotic surgery is generally reported to take longer than conventional open or endoscopic surgery. The prolonged operation time has been attributed to the need for docking and setup of the robotic arms [20,21,35]. In the present patient series, the mean total operation time for total thyroidectomy was 132 min.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Robotic surgery is generally reported to take longer than conventional open or endoscopic surgery. The prolonged operation time has been attributed to the need for docking and setup of the robotic arms [20,21,35]. In the present patient series, the mean total operation time for total thyroidectomy was 132 min.…”
Section: Discussionmentioning
confidence: 77%
“…Initial clinical trials have shown that robotics can enhance the precision and accuracy of dissection and can improve handling [19]. Another major benefit of robotic surgery is the stable camera platform held by the robotic arm [20,21]. Such stability assists lymph node dissection by enabling more precise movement of instruments around the vessels and nerves.…”
Section: Discussionmentioning
confidence: 99%
“…As we gain more experience, we expect the operating time to fall even further and be similar to the open method. The advanced technology in the robotic surgical system shortens the time of actual operative procedure itself, because it mimics intuitively the open procedure as opposed to the laparoscopic procedure in which surgical maneuvering is counterintuitive [4,5] The estimated blood loss was significantly less in roboticassisted surgery compared with the open method (165.14 vs 406.04 ml). Magnified vision and improved dexterity helps in better vascular control than the open method.…”
Section: Discussionmentioning
confidence: 99%
“…Предыдущие клинические иссле-дования показали техническую выполнимость и безопасность данной операции не только при доброкачественных, но и при злокачественных новообразованиях толстой кишки [18].…”
Section: роботизированные операции на ободочной кишкеunclassified
“…Роботическая низкая передняя резекция -относительно редкая операция по сравнению с остальными вмешательствами на толстой кишке [15,18,[19][20][21][22]24,25,32,33]. Хирургиче-ская техника при операциях на прямой киш-ке является наиболее сложной по сравнению с другими вмешательствами, что обусловлено ограниченностью пространства полости мало-го таза и наличием большого количества важ-ных анатомических структур в этой области.…”
Section: роботизированные операции на прямой кишкеunclassified